2006
DOI: 10.1002/ppul.20493
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the prevalence of urinary incontinence in girls with cystic fibrosis, asthma, and healthy controls

Abstract: Urinary incontinence (UI) is recognized as a significant problem in adult females with cystic fibrosis and can often have a marked impact on day-to-day activities. The prevalence and severity of UI in the pediatric cystic fibrosis (CF) female population is less clear and there are no comparative data with healthy children or children with other respiratory disorders. An anonymous self-completed semi-structured questionnaire was used to study the prevalence rates of UI in girls with CF aged between 11 and 17 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 13 publications
3
32
1
Order By: Relevance
“…There have been many studies regarding UI issues in populations of women with CF. Most of them reported a much higher prevalence of incontinence in the CF population than in healthy young people [4,6,7], but some authors reported that incidence of urinary incontinence is no different between adolescents with CF, and controls [3]. We authors realize, that the lack of a control group is the main limitation of this study, nevertheless, our results highlight that the UI prevalence is very high in Polish female adolescents with CF.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…There have been many studies regarding UI issues in populations of women with CF. Most of them reported a much higher prevalence of incontinence in the CF population than in healthy young people [4,6,7], but some authors reported that incidence of urinary incontinence is no different between adolescents with CF, and controls [3]. We authors realize, that the lack of a control group is the main limitation of this study, nevertheless, our results highlight that the UI prevalence is very high in Polish female adolescents with CF.…”
Section: Discussioncontrasting
confidence: 51%
“…There have been many studies in the world regarding UI in adolescent females with CF [3][4][5][6]. However in Poland, where we observe the improved life expectancy in these patients, there is no data regarding that issue.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…While most of the studies described the urinary leakage as stress incontinence, urge incontinence was reported in 11-50% of females with cystic fibrosis [14] . Both women and girls who leak were shown to have more severe lung disease (worse forced expiratory volume 1, more severe cough, and more sputum production) than those without a problem [11,12] .…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence for the association between chronic cough and UI comes from the cystic fibrosis literature. UI is now an established concern for women and girls with cystic fibrosis with a prevalence ranging from 30 to 69% for women and 19 to 49% for girls [10][11][12][13][14] , which is higher than that for the general population. The major cause of UI in these patients has been attributed to the stress placed on the pelvic floor by repeated coughing and forced expiratory maneuvers [13,14] .…”
Section: Discussionmentioning
confidence: 99%